Apolipoprotein C1 (APOC1): A Novel Diagnostic and Prognostic Biomarker for Clear Cell Renal Cell Carcinoma - Cui, Yankang; Miao, Chenkui; Hou, Chao; Wang, Zengjun; Liu, Bianjiang (Frontiers in Oncology, 2020)
Abstract Background: Apolipoprotein C1 (APOC1) has been proved to play a critical role in gastric, breast, lung and pancreatic cancer. However, the relationship between APOC1 and urinary tumors remains unclear. This study aimed to assess the diagnostic and prognostic value of APOC1 in urinary tumors. Methods: We performed a pan analysis of APOC1 mRNA expression in urinary cancer using the Gene Expression Profiling Interactive Analysis (GEPIA) database. To further investigate the prognostic value of APOC1 expression in urinary cancers, the Kaplan-Meier plotter database was used. Furthermore, we collected the tumor and adjacent normal samples of 32 ccRCC patients to perform qRT-PCR and western blotting assays. A total of 72 cases with ccRCC were analyzed using tissue microarrays (TMAs). Results: Our results basing on Kaplan-Meier plotter database indicated that a high expression of APOC1 may lead to poor overall survival (OS, p = 0.0019) in patients with ccRCC. Furthermore, the cancer stages and tumor grade of ccRCC appeared to be strongly linked with APOC1 expression according to UALCAN database. Hence, we reached a preliminary conclusion that APOC1 may play a key role in the tumorigenesis and progression of ccRCC. Furthermore, the Kaplan-Meier survival curve analyses of 72 clinical patients indicated that high expression of APOC1 was associated with poor progression-free survival (PFS, p = 0.007) and OS (p = 0.022). Besides, univariate Cox regression analysis confirmed the significant relationship between APOC1 expression and survival(p=0.038). The TMAs analysis in combination with the patients' clinicopathological features was also performed. The expression of APOC1 was found to be significantly correlated with the tumor size (p = 0.018) and histological grade (p = 0.016). Conclusions: In conclusion, the findings of our study suggest that APOC1 may serve as a novel diagnostic and prognostic biomarker for ccRCC. Further evidence on the mechanism of APOC1 promoting tumor progression may transform it to a new therapeutic target for the treatment of ccRCC.